2016
DOI: 10.1037/ebs0000056
|View full text |Cite
|
Sign up to set email alerts
|

The development of the child unpredictability schema: Regulation through maternal life history trade-offs.

Abstract: Guided by life history theory, the present study (a) developed and provided preliminary validation data for a self-report measure of a childhood unpredictability schema (i.e., a worldview where children perceive other people and future outcomes as unreliable and unpredictable) and (b) tested for the effects of maternal life history strategy and its behavioral components on development of the child's unpredictability schema. Because maternal life history strategy may impact her child's physical, mental, and cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 58 publications
2
39
0
Order By: Relevance
“…Growing up under such household conditions should orient individuals to prioritize mating effort over parental obligations and impact the development of children. Consistent with this view, research examining low-income mothers and their elementary school children found that both decreased parental effort and increased mating effort were associated with a more highly developed child unpredictability schema [15 • ]. Retrospective examination of family unpredictability designated by inconsistency in discipline/nurturance, family meals, and income was associated with a more developed unpredictability schema in college students [16].…”
Section: Psychosocial Acceleration Theory: a Primermentioning
confidence: 98%
See 1 more Smart Citation
“…Growing up under such household conditions should orient individuals to prioritize mating effort over parental obligations and impact the development of children. Consistent with this view, research examining low-income mothers and their elementary school children found that both decreased parental effort and increased mating effort were associated with a more highly developed child unpredictability schema [15 • ]. Retrospective examination of family unpredictability designated by inconsistency in discipline/nurturance, family meals, and income was associated with a more developed unpredictability schema in college students [16].…”
Section: Psychosocial Acceleration Theory: a Primermentioning
confidence: 98%
“…, moving residences and schools, changes in caregivers and/or parental relationships [1214]). Work focusing on the unpredictability schema has found a link between these family-level indicators of unpredictability and increased perception of unpredictability [15 • ,16]. Growing up under such household conditions should orient individuals to prioritize mating effort over parental obligations and impact the development of children.…”
Section: Psychosocial Acceleration Theory: a Primermentioning
confidence: 99%
“…An antagonistic behavioral strategy should be enacted by schemas and a worldview that conspecifics and the environment is unreliable (Ross & Hill, 2002). Recent evidence suggests that low-investing maternal parenting predicted greater perceptions of unpredictability in middle childhood (Cabeza de Baca, Barnett, & Ellis, 2016). Prior experience with violent events also appears to increase risk perceptions of future hazardous events in adults (Blum et al, 2014) and post-traumatic stress symptomatology in children (Garfin et al, 2014).…”
Section: Life History Theorymentioning
confidence: 99%
“…In humans, childhood adversity and family unpredictability have been implicated in the development of a childhood unpredictability schema that is associated with future discounting, impulsivity, and risk taking ( Hill et al, 1997 ; Ross and Hill, 2002 ; Cabeza de Baca et al, 2016 ). These unpredictability schema may in turn shape our internalized working models of attachment and ultimately our perceptions of social support and how we perceive others will react to meeting our needs ( Collins and Feeney, 2004 ).…”
Section: Mismatches Between Life History Strategy and The Environmentmentioning
confidence: 99%